1987
DOI: 10.1159/000248998
|View full text |Cite
|
Sign up to set email alerts
|

Cell Kinetics of the Human Anagen Hair Follicle

Abstract: Anagen hair follicles obtained from both healthy (n = 7) and uninvolved psoriatic (n = 4) scalps were segmentally analyzed for proliferative activity using DNA flow cytometry. Hair follicle kinetics were almost equal in either group except for the infundibular portion which exhibited significant increase of S-phase values in psoriatic patients. Maximum proliferation was disclosed within the bulbar segment. This study confirms that cell kinetics behavior of hair follicles from uninvolved scalp of psoriatics com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…More recent data based on flow cytometric studies have shown altered cell kinetics only in the infundibular portions of the follicle. 3 Morphological studies of the differentiated products of hair matrix epithelium in psoriasis, ie, the cuticular layers, the inner sheath layers, and the hair shaft, have documented only minor morphologi¬ cal changes in the hair shaft cuticle4 and, of particu¬ lar interest, thinner hair shafts.45…”
mentioning
confidence: 99%
“…More recent data based on flow cytometric studies have shown altered cell kinetics only in the infundibular portions of the follicle. 3 Morphological studies of the differentiated products of hair matrix epithelium in psoriasis, ie, the cuticular layers, the inner sheath layers, and the hair shaft, have documented only minor morphologi¬ cal changes in the hair shaft cuticle4 and, of particu¬ lar interest, thinner hair shafts.45…”
mentioning
confidence: 99%